PRESCHOOL EDUCATION SYSTEM IN JAPANESE EDUCATION SYSTEM - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
In this article, the best practices of preschool education and upbringing in foreign countries are studied on the basis of comparative analysis. Mainly information is provided about the forms of preschool education in developed Western and Eastern countries and the Japanese preschool education system. Also, special attention is paid to the researches conducted in connection with the study of foreign experiences related to preschool education and upbringing. Clear ideas about its methodological basis are stated. The role and importance of the best practices in the education system in ensuring the development of the states is revealed.